2012
DOI: 10.4293/108680812x13291597715781
|View full text |Cite
|
Sign up to set email alerts
|

BioGlue Surgical Adhesive as a Thermal Reflector During Laparoscopic Cryoablation: Effect on Iceball Size and Ablation Zone Diameter

Abstract: In a porcine model, the application of BioGlue did not appear to increase the size of the iceball generated, nor did it change the amount of subjective bleeding noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Although not yet specific on a molecular level, current thermal-ablative approaches do have a high demonstrated success rate with up to 97% positive response using RFA and 98% using LITT for treatment of breast metastases [103] and colorectal cancer metastases [104]. Cryoablation alternatively uses localized low temperatures to freeze and kill neoplastic tissue [105]. Our laboratory demonstrated that DNA-encased MWNTs had the capacity to thermally eradicate prostate cancer xenografts [74] in nude mice model upon near-infrared(NIR) radiation, without causing significant damage to the adjacent tissue.…”
Section: Thermal Ablative Approaches To Cancer Treatmentmentioning
confidence: 99%
“…Although not yet specific on a molecular level, current thermal-ablative approaches do have a high demonstrated success rate with up to 97% positive response using RFA and 98% using LITT for treatment of breast metastases [103] and colorectal cancer metastases [104]. Cryoablation alternatively uses localized low temperatures to freeze and kill neoplastic tissue [105]. Our laboratory demonstrated that DNA-encased MWNTs had the capacity to thermally eradicate prostate cancer xenografts [74] in nude mice model upon near-infrared(NIR) radiation, without causing significant damage to the adjacent tissue.…”
Section: Thermal Ablative Approaches To Cancer Treatmentmentioning
confidence: 99%
“…Although not yet specific on a molecular level, current thermal-ablative approaches do have a high demonstrated success rate with up to 97% positive response using RFA and 98% using LITT for treatment of breast metastases [103] and colorectal cancer metastases [104]. Cryoablation alternatively uses localized low temperatures to freeze and kill neoplastic tissue [105]. Our laboratory demonstrated that DNA-encased MWNTs had the capacity to thermally eradicate prostate cancer xenografts [74] in nude mice model upon near-infrared(NIR) radiation, without causing significant damage to the adjacent tissue.…”
Section: Np-mediated Cancer Treatmentmentioning
confidence: 99%